Socio-Economic Welfare Clustering: A Sub-National Governments Analysis In Indonesia - Ayu Aryawati; Mulya Amri; Raden Aswin Rahadi (Green Publisher Indonesia, 2025)
Indonesia, as the world's largest archipelagic nation, encounters challenges in achieving equitable development and socio-economic well-being across its diverse regions. To address developmental disparities, the central government allocates specific purpose grants, the amount of which is tailored to the development needs of each region. Additionally, Indonesia has established a development financial institution aimed at providing financing and capacity-building support to SNGs in planning and implementing regional development initiatives. In determining the priority of grant allocation, financing, and capacity building, a tool is needed to identify disparities in socio-economic welfare between one SNG and other SNGs in Indonesia. This study examines the use of the clustering method with a K-means approach to group SNGs based on similarity in socio-economic welfare. This study employs Poverty rate, Human Development Index and Gross Regional Development Product per capita from 2021 to 2023 as variables input. At the end of the study, four clusters of SNGs in Indonesia were obtained based on their level of socio-economic welfare.